ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMA BEASISWA BIDIKMISI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA UNIVERSITAS JAMBI - Farhan, Muhammad; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2018)
Bidikmisi scholarship program is a government program to provide access to higher education to people who are economically disadvantaged and have the academic potential to be able to break the poverty chain. This program has a philosophy of picking up recipients. The selection process for bidikmisi scholarship recipients is based on criteria determined by the Ministry of Research Technology and Higher Education and university jambi. In computer science there is a system that can assist in the selection and decision making process to produce more effective and accurate decisions. In Decision Supporting Systems there are various methods, one of them is the Simple Additive Weighting (SAW) method. The basic concept of the Simple Additive Weighting (SAW) method is to find the weighted sum of performance ratings for each alternative on all criteria. Tests are carried out with student data from alternative scholarship recipients who will be normalized according to the criteria attribute (benefit or cost). The final result is obtained from the calculation process, which is the sum of the normalized matrix with the weight per criteria that shows the alternative rank of scholarship recipients. It is expected that the results of this study can help decision makers in determining the bidikmisi scholarship recipients